1999
DOI: 10.1889/1.1834078
|View full text |Cite
|
Sign up to set email alerts
|

P‐22: Improvement of Luminance Efficiency in an ACPDP by Self‐Erase Discharge Waveform

Abstract: This paper describes a novel waveform which improved the luminance efficiency of AC‐PDP without reducing the voltage margin. This waveform which induces self‐erase discharges by space charges, utilizes the memory effect of space charges like the puke memory of DC‐PDP, in addition to the memory effect of wall charges. More than a 15% higher efficiency is obtained in the 40‐inch diagonal XGA AC‐PDP developed by us when compared with the conventional waveform at the same operating point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…There are some approaches to applying sustain waveforms that induce self-erase discharges in the static voltage margin. [19][20][21][22][23][24] Jeong et al, 20 after measuring the wall charge distribution, reported the real operation condition of ac PDPs: when the address electrode is grounded, the self-erase discharge occurs mainly between the sustain and address electrodes. Thus, the luminance and luminous efficacy show their maxima at voltages much lower than those values of the case of the address electrode floated as can be seen from Fig.…”
Section: Self-erase Dischargementioning
confidence: 99%
See 1 more Smart Citation
“…There are some approaches to applying sustain waveforms that induce self-erase discharges in the static voltage margin. [19][20][21][22][23][24] Jeong et al, 20 after measuring the wall charge distribution, reported the real operation condition of ac PDPs: when the address electrode is grounded, the self-erase discharge occurs mainly between the sustain and address electrodes. Thus, the luminance and luminous efficacy show their maxima at voltages much lower than those values of the case of the address electrode floated as can be seen from Fig.…”
Section: Self-erase Dischargementioning
confidence: 99%
“…9,10,16,17 Also, researchers have suggested several modified driving waveforms taking advantage of the self-erase discharge characteristics of PDPs to improve luminous efficacy. [19][20][21][22][23][24] Lo et al 19 reported that the self-erase discharge induced between coplanar electrodes and a floating address electrode by applying higher voltage to coplanar electrodes can result in an increase in luminous efficacy with decreased consumed power. Also the luminous efficacy also improved by applying short pulses to the address electrode increasing the self-erase discharge intensity in the conventional small gap structure with a low Xe contents gas mixture condition.…”
Section: Introductionmentioning
confidence: 99%
“…그 중 구동방법에 있어서의 효율 개선에 있어서는 유지기간 중에 에너지회수회로의 개선과 자기소거 방전을 발생시키는 노력에 초점이 맞 춰져 왔다 [3][4] . 자기소거 방전이란 유지기간 중에 전압 에 의한 주방전 외에 전압이 인가되지 않는 시간동안 한번 더 발생되는 방전이므로 휘도효율을 크게 향상시 킨다고 보고되어왔다 [5] .…”
unclassified
“…A large number of alternative waveforms with improved efficiency have been proposed [12]- [21]. Most of them are based on alternative driving voltage schemes with frequencies in the conventional 50-350 kHz range [12]- [18].…”
mentioning
confidence: 99%
“…A large number of alternative waveforms with improved efficiency have been proposed [12]- [21]. Most of them are based on alternative driving voltage schemes with frequencies in the conventional 50-350 kHz range [12]- [18]. Recently, the use of radio-frequency (RF) voltages around 50 MHz has been proposed to replace the conventional sustaining voltage [19], [20].…”
mentioning
confidence: 99%